THE TEACHING OF ENGLISH GRAMMAR IN THE INDONESIAN CONTEXT: THE STATE OF THE ART - Utami Widiati; Bambang Yudi Cahyono (Celt: A Journal of Culture, English Language Teaching & Literature, 2006)
As an important element of language and as the essential part of linguistic competence, grammar has a central role in making up learners language skills and their communicative competence. However, from the historical perspective of language teaching methodology, the role of grammar has once been over-emphasized, likely neglected, or treated equally important with fluency in communication. This article reviews aspects of the teaching of grammar, varying from common issues of grammar teaching in the broader perspective of foreign/second language learning to the teaching of grammar as well as research on grammar teaching in the Indonesian context. In light of the discussion of these various issues, this article provides some recommendations for future research and insights for addressing grammar in English language classrooms in Indonesia.